Limitations of functioning in everyday life in women surgically treated for breast cancer - Rząca, Marcin Stanisław; Łukasiewicz, Sergiusz; Sołowiej, Krzysztof; Stanisławek, Andrzej; Domżał-Drzewicka, Renata (Journal of Education, Health and Sport, 2019)
Admission: The primary method of treatment more frequently occurring breast cancer is surgery. The occurrence of secondary lymphedema and other symptoms of upper limb can reduce the efficiency of the patient causing hindering her daily life and functioning.The goal of the work It is to present a range of restrictions on daily functioning in patients surgically treated for breast cancer associated with the changes occurring in the limb on the side of the operated breast,Material and methods: The material consisted of 151 women treated surgically for breast cancer (T1-4 N0-3 M0) in the Oncology Center of the Lublin Region St. John of Dukla in Lublin in 2013-2015. Secondary lymphedema after 6 months occurred in 19.2% of patients.Results: Difficulties functioning in daily life due to limitations arising after surgery upper limb occurred in half of the respondents. Limiting the strength of the limb that hinders daily caring activities occurred in 4% of all subjects and making home work difficult at 40%. Reducing the precision movements of the limbs impeding daily activities nursing occurred in 13% of patients and impeding the exercise of precise steps in 9%.Conclusions:1. The frequency present difficulties in the daily operation applied to the anticancer treatment is high.2. The frequency present difficulties in daily functioning is higher in subjects treated with more invasive surgical treatment.3. The presence of the secondary lymphedema patients experience difficulties with daily activities, especially precise.